2020
DOI: 10.1002/dc.24644
|View full text |Cite
|
Sign up to set email alerts
|

A correlation study between thyroid imaging report and data systems and the Bethesda system for reporting thyroid cytology with surgical follow‐up an ultrasound‐trained cytopathologist's experience

Abstract: Introduction Thyroid Imaging Reporting and Data Systems (TI‐RADS) including a modified system (M TI‐RADS) and American College Radiology (ACR) TI‐RADS are introduced. Correlation studies between both TI‐RADSs and The Bethesda System for Reporting Thyroid Cytology (TBSRTC) for Ultrasound‐guided fine‐needle aspiration (US‐FNA) cases with surgical follow‐up (SFU) are presented. Materials and Methods Three hundred and forty six thyroid US‐FNA cases performed at the US‐FNA clinic of Stony Brook University Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…21 What made the present study different from almost all of the other studies was that it had final pathology results as well as Bethesda scores. 15,19,20 The current study has the highest positive correlation reported in the literature between the ACR TI-RADS and the Bethesda system. The reason why this very strong positive correlation (ρ = 0.832) was found between both classifications may be the intense focus on the Bethesda scoring system and the ACR TI-RADS relationship.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…21 What made the present study different from almost all of the other studies was that it had final pathology results as well as Bethesda scores. 15,19,20 The current study has the highest positive correlation reported in the literature between the ACR TI-RADS and the Bethesda system. The reason why this very strong positive correlation (ρ = 0.832) was found between both classifications may be the intense focus on the Bethesda scoring system and the ACR TI-RADS relationship.…”
Section: Discussionmentioning
confidence: 55%
“…It was noted that modified TI-RADS correlated slightly better than ACR TI-RADS. 19 Modi et al evaluated 361 thyroid nodules classified by ACR TI-RADS and showed that this classification is more successful in detecting malignant lesions. A Bethesda score of 6 was noted in 14 cases with TR5; however, it was found that ACR TI-RADS was more successful, especially in TR4 and TR5 categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found an overall 0.465 r-value between TI-RADS scores and TBSRTC categories. Furthermore, the comparative analysis between TBSRTC and TIRADS showed that sensitivity, specificity, PPV, NPV, and accuracy are 96%, 53%, 76%, 89%, 79% for TI-RADS vs. 100%, 93%, 96%, 100%, 97% for TBSRTC, respectively (p = 0.038) [39].…”
Section: Results From Applying Tiradsmentioning
confidence: 96%
“…Various studies have evaluated the prediction of thyroid malignancy using TIRADS [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Table 3). Shayganfar et al studied 239 thyroid nodules combining TIRADS and FNA outcome using the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) [25].…”
Section: Results From Applying Tiradsmentioning
confidence: 99%